Pengembangan UMKM dengan Penerapan Green Financing di Kota Medan: Analisis Kualitatif Terhadap Dampak dan Tantangan - Hakim, Andy; Ar Rahmah, Rizka; Harahap, Mufti Fahrizal; Rosvita, Rosvita; Maulida, Nur; Rahmasari, Devi (Universitas Pahlawan Tuanku Tambusai, 2024)
Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in Indonesia's economy, but the adoption of sustainability principles remains low. Green financing offers a solution to support environmentally friendly projects that can enhance the economic and environmental sustainability of MSMEs in Medan City. This study employs a qualitative approach with in-depth interviews and document studies. Data were collected from MSME owners in Medan City and analyzed using triangulation techniques to ensure the validity of the research findings. The study found that awareness and understanding of green financing among MSME actors are still low. Access to green financing is also limited due to stringent requirements and complicated procedures. However, MSMEs that successfully accessed green financing reported significant economic and environmental benefits, including operational cost efficiency and carbon emission reductions. The main challenges in implementing green financing are the lack of technical support and skills among MSME actors. Green financing has great potential to improve the sustainability of MSMEs in Medan City, but further efforts are needed to enhance accessibility and understanding. The government and financial institutions play a key role in providing supportive policies and special financing programs. Intensive education and socialization are necessary to raise awareness about the benefits of green financing. Collaboration between the government, financial institutions, and NGOs is crucial to creating an ecosystem that supports the sustainable development of MSMEs.